And she was : a verse-novel - Corbett, Sarah, 1970- (Pavilion Poetry., 2015)
A soul's journey through the night, a missing woman: time and narrative bend and interlock across a play of poetic forms and voices to make one story of love and loss. In And She Was Corbett combines the fictional spell-making of Haruki Murakami, with the filmic neo-noir of Atom Egoyan (Exotica) and David Lynch (Lost Highway, Mulholland Drive), to push the boundaries of poetic genre, asking us to renegotiate the way we encounter and reconfigure ourselves through trauma, in desire, or as we seek to reassemble ourselves and our past. November, 3am, and two young lovers are about to meet on the Heathrow Express. A side street in an unknown city: Felix Morning wakes with no memory. In his pocket is a membership card for a nightclub, The Bunker. With the help of the beautiful Flick, he must recover what he has lost. Deep into a dangerous love affair, Esther and Iain believe the other can replace what they each have lost - a heart, a gift - but is Esther's price too high for Iain to pay, ...